The effect of silver-ion water on the growth of Streptococcus mutans - Wicaksono, Dimas Prasetianto; Tedjosasongko, Udijanto; Dewi, Ardianti Maartrina; Sinaredi, Betadion Rizki; Setiawati, Herautami Caezar Yulia; Reviany, Meylan; Octaviana, Surya Anastasya; Laosuwan, Kittipong (Indonesian Journal of Dental Medicine, 2024)
Background: Caries is a multifactorial disease that often occurs in the oral cavity and can be caused by Streptococcus mutans. Various ways have been done to reduce the number of Streptococcus mutans, one of them is by exposing them to a material agent such as silver-ion water. Silver-ion water has been recognized as an effective material for inhibiting several pathogenic bacteria, such as Staphylococcus aureus and Escherichia coli. Thus, there is a possibility that silver-ion water can be used to reduce the number of bacteria that cause dental caries, such as Streptococcus mutans. Purpose: To determine the effect of silver ion water on the growth of Streptococcus mutans. Methods: This research is an experimental laboratory study (in vitro) with a control group post-test-only design. Streptococcus mutans were exposed to 0-15 ppm silver-ion water on Brain Heart Infusion Broth (BHIB) media, then Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were observed. Results: Silver-ion water with a concentration of 12.5 ppm was determined as MIC, and silver-ion water with a concentration of 15 ppm as MBC. Conclusion: Silver ion water is adequate as an antibacterial material in inhibiting (12.5 ppm) and killing (15 ppm) Streptococcus mutans.